Didactic guide for non-bilingual teachers to teach in a third grade in camilo torres school sede jorge eliecer gaitan based on the clil method (2016)
This research is based on the creation and implementation of a didactic guide specially designed for non-bilingual teachers in third grade in a public school. This guide pretends to be an aid for the teacher whose level on the target language is not enough to teach it; that is why, it contains instructions on how they should teach the English language, but taking into account the CLIL (Content and Language Integrated Learning) Method. This is a qualitative research in which the use of observation and interviews were important to its development. As a result, the teacher felt more confident because he knew how to carry out an English class with a clear sequence and entertained activities that made students be more engaged with the class and the learning of the language.